Characterization of Intracellular Peptides from Zebrafish (Danio rerio) Brain - Manzi Teixeira, Caio Matheus [UNESP]; Correa, Claudia Neves [UNESP]; Iwai, Leo Kei; Ferro, Emer Suavinho; Castro, Leandro Mantovani de [UNESP] (Mary Ann Liebert, Inc, 2019)
Peptides represent a large class of cell signaling molecules, and they are mainly produced by the classical secretory pathway or during protein degradation. The peptide profile of Danio rerio (zebrafish) shows a lack of information when compared with other consolidated animal models. The aim of this work was to characterize the peptide profile of zebrafish brain by using triplex reductive methylation of amines labeling and liquid chromatography coupled to electron spray mass spectrometry. A total of 411 peptide fragments were detected and 125 peptide sequences could be solved. Further analysis suggested that most of the peptides were fragments of intracellular cytosolic and mitochondrial proteins, and that 60% of the precursor proteins were cleaved at either their N- or C-terminal. The most common residue in the P1 position was leucine whereas other common residues were lysine, alanine, arginine, and phenylalanine. Rare cleavage sites at P1 position were histidine, glutamic acid, and isoleucine. The peptide profile of zebrafish brain has similarities with results previously described in mice brain peptidome studies. Thus, this study represents an important basis for the molecular understanding of zebrafish and its use as a model for human diseases.
Keywords: intracellular peptides; peptidome; nervous system; mass spectrometry